Ecologia e tassonomia del genere Rhodocybe R. Maire (Basidiomycetes, Entolomataceae) in Sardegna - Contu, Marco (Revista Catalana de Micologia, 2007)
The species of the genus Rhodocybe occurring in Sardinia are keyed-in, described and taxonomically discussed. At the time being 16 entities are known to occurr in the Isle.